Screening for non-classic congenital adrenal hyperplasia in women: New insights using different immunoassays - Nakhleh, Afif; Saiegh, Leonard; Shehadeh, Naim; Weintrob, Naomi; Sheikh-Ahmad, Mohammad; Supino-Rosin, Lia; Alboim, Sandra; Gendelman, Raya; Zloczower, Moshe (Frontiers in Endocrinology, 2023)
Context: The 250µg-cosyntropin stimulation test (CST) is used to diagnose non-classic congenital adrenal hyperplasia (NCCAH). The current recommendation is to perform CST when follicular 17-hydroxyprogesterone (17OHP) is 6-30 nmol/L, a cutoff derived from radioimmunoassay (RIA). Recently, enzyme-linked immunosorbent assay (ELISA) has replaced RIA. Objectives: We aimed to (1) determine the RIA and ELISA-based 17OHP cutoffs at which CST should be performed, (2) identify predictors of NCCAH. Methods: A retrospective study at an Israeli Health Maintenance Organization. Data were retrieved from women with suspected NCCAH, referred for CST during 2001–2020. NCCAH was defined as a stimulated 17OHP >30 nmol/L. Serum 17OHP levels were assayed by RIA from 1/2000-3/2015, and by ELISA from 4/2015-12/2020. ROC curves were generated and optimal 17OHP thresholds were determined. Multivariate analysis was performed. Results: CST was performed in 2409 women (1564 in RIA, 845 in ELISA). NCCAH was diagnosed in 4.7% of the RIA group and 7.5% of the ELISA group. The optimal basal 17OHP cutoff values predicting NCCAH were 6.1 nmol/L in RIA (sensitivity=93.2%, specificity=91.7%) and 8.2 nmol/L in ELISA (sensitivity=93.7%, specificity=92.3%). In multivariate analysis, higher basal 17OHP, lower LH:FSH ratio, and oligomenorrhea were predictors of NCCAH in RIA. Higher basal 17OHP, androstenedione, and total testosterone were predictors of NCCAH in ELISA. A lower LH:FSH ratio showed similar trend in ELISA. Conclusions: Optimal RIA-based basal 17OHP cutoff was comparable with that recommended in guidelines. The results suggest adopting a higher 17OHP cutoff when using ELISA. LH:FSH ratio improves the negative predictive value of basal 17OHP.